(3hSGFd GdGJUGd (B:s (3EYdGe(B- (3YdGbGJ YeI(B- (3OYGjI h GYdGf(B- (3QGj YGe(B- (3IGJUGdGJ(B- (3JhGUd (B/s - (3GdeHjVjf, YHO GdQMeGf eMeOs ((3YeGf (B- (3GdCQOf (B:s (3OGQ GdHQcI ddfTQ h GdJhRjY ,s, 2001)
(3gPG GdcJGH KeQI deYQaI h NHQI WhjdI MjK JfGhd aj aUhdg GdGhdi GdLhGfH GdfXQjI dehVhY GdGJUGd ef MjK JYQjag h GgejJg eQcRG Ydi GdYdGbGJ GdYGeI h GdOYGjI h GdGYdGe h GdQCj GdYGe HGdTQM h GdJMdjd h GdfbO h GdJTLjY h GdJMPjQ Ke GfJbd aj aUhdg GddGMbI dJfGhd GdJSdSd GdJGQjNj ddGOhGJ h GdGLgRI GdJj GSJYedJ chSGFd Jfbd GdeYdheI ef h Gdi GbWGH YedjI GdGJUGd cGdJdcS h GdaGcS h GdQGOjh h GdJjdjaRjhf eHfjG GdJWhQ GdPj WQG Ydi OhQ cd LgGR Gh GdI ef gPg GdGdGJ h GgejI cd efgG aj GdYedjI GdGYdGfjI h GdGYdGejI Ydi GdShGAs
Keywords: (3OYGjI s; (3YdGbGJ YGeIs; (3GdEYdGes; (3hSGFd GdEYdGes